PENGARUH MODEL PEMBELAJARAN BERBASIS WEB DAN KEAKTIFAN TERHADAP PRESTASI BELAJAR SISWA - Sudarman Sotar Sitorus; Riyanto (DIADIK, 2023)
This research aims to determine the effect of using web-based learning models on student achievement in social studies subjects grade 8 junior high school of SMP Swasta Sint Carolus Bengkulu. The implementation of research is carried out in the first semester of the school year 2020/2021, and the implementation time is adjusted to the time allocation for the delivery of the 8th grade social sience subject matter “Geographical Conditions Of ASEAN Countries”. The study used an experimental method with a two-way ANOVA factorial design. The population in this study were students of class VIII as many as 119 students consisting of four classes. The sample in this study were students of class VIIID as the experimental class totaling 18 students and class VIIIC as the control class totaling 18 students. Conclusion from this research include: 1) Student achievement using the google earth application learning media is higher than using a map. 2) High learning activity student achievement is better than low learning activity student. 3) There is no significant interaction between web-based learnig media and activity on student achievement